Does the Advance Medical Directive Encourage Active Euthanasia? - Mohd Zamre Mohd Zahir, Ramalinggam Rajamanickam, Haniwarda Yaakob, Nur Khalidah Dahlan, Husyairi Harunarashid, Suhaizad Saifuddin (South Eastern European Journal of Public Health, 2025)
An Advance Medical Directive (AMD) is a person’s instructions for his future treatment decisions. Does the AMD encourage active euthanasia? Active euthanasia occurs when death is caused by an act, such as administering an overdose of painkillers or injecting a person with a deadly dose of a substance to end his life. An active euthanasia is also prohibited. While implementing AMD, there is uncertainty about the law that will bind it. However, critics contend that some of AMD’s wording could be read in ways that support euthanasia-like procedures. For instance, a directive expressing a preference for “no extraordinary measures” may be interpreted incorrectly, especially in places with unclear legal definitions of euthanasia, withdrawal of treatment, and palliative care. Thus, this paper aims to analyse the law and ethical aspects concerning AMD in Malaysia. This paper adopts a qualitative methodology. The types of main and secondary sources of literature on AMD, medical law, and ethics are examined by the authors. This study concluded that while discussing AMD in Malaysia, Articles 17 and 18 of Consent for Treatment of Patients by Registered Medical Practitioners from the Malaysian Medical Council (MMC) can be cited. Therefore, this study argues that it is crucial for Malaysia to have more precise guidelines regarding AMD and the issue of active euthanasia.